Motivasi Kerja Pustakawan di Perpustakaan Politeknik Pertanian Universitas Andalas Payakumbuh - Chandra, Erik Septian; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This study aimed to describe: work motivation Politani librarian at the Library, the forms of motivation given leadership to the librarian, and the difficulties inmotivating librarians working in the Library Politani. Data were collected through interviews and observations in the Library Politani. The data were analyzed descriptively. Technique of analyzingdata is done by describing the interview, describing the results of direct observation, data has been obtained in accordance with the theory discussed, conclusions, and reporting. The results of this study are as follows: (1) motivation librarians already exist in it self, but the implementation is still not good, (2) forms of motivation given to the librarian leadership Politani Library is extrinsic motivation in the form of gifts, and advice orally (ego-involvement), (3)difficulties in motivating librarians motivation is difficult to determine the most appropriate tool for each individualis not the same desire, the ability Library Politani limited in providing facilities, library leaders work hard to know the motivation of each individual librarians. Keywords: motivation; librarian; library leaders